(untitled) (Damu Journal of Sport Sciences, 2025)
Through the researcher's observation and analysis of numerous basketball matches in Iraq and interviews with numerous coaches of local and popular teams, he indicated a weakness and inaccuracy in mastering the long-range shooting skill. The researcher attributes one of the reasons for this fluctuation to the lack of use of modern technological media, which led to this situation, which the researcher found worthy of study. Therefore, the research problem was embodied in studying the possibility of using technological media in learning, and its role in helping learners learn the accuracy of long-range shooting by jumping in basketball. Through the development of technological media for learning, the researcher found that there was a pressing need for something to be scientifically changed to contribute to the development of the educational process. The research aims to: Develop an educational program using technological media to develop the accuracy of long-range shooting by jumping with a basketball, and to determine the impact of an educational program using technological media on developing the accuracy of long-range shooting by jumping with a basketball. The researcher concluded that the use of multimedia technology contributed effectively to learning the technical performance of the long-range shooting skill in basketball for players aged 16-17 years.